2015
DOI: 10.1039/c4an01639d
|View full text |Cite
|
Sign up to set email alerts
|

Correlating enzyme density, conformation and activity on nanoparticle surfaces in highly functional bio-nanocomposites

Abstract: The biological activity of the immobilized enzyme is crucial for the performance of different nanoparticle mediated enzymatic assays, where enzymatic conversion can be used for label-free analyte detection. In this article we have addressed two significant aspects of enzyme-nanoparticle interactions. First, we have developed copper sulfide (CuS) nanoparticles with an average diameter of 25 nm as a potential enzyme-interface using trypsin protease as a model enzyme. CuS nanoparticles showed high trypsin immobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 40 publications
4
29
0
Order By: Relevance
“…Based on Saha et al. the molecular dimension of native trypsin from porcine pancreas is 4.8 nm x 3.7 nm x 3.2 nm. Assuming that the spatial dimensions of bovine‐derived trypsin are similar and that enzyme molecules are surrounded by a hydration layer of approximately 0.2 nm, one trypsin molecule would occupy between 10 and 20 nm 2 surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Saha et al. the molecular dimension of native trypsin from porcine pancreas is 4.8 nm x 3.7 nm x 3.2 nm. Assuming that the spatial dimensions of bovine‐derived trypsin are similar and that enzyme molecules are surrounded by a hydration layer of approximately 0.2 nm, one trypsin molecule would occupy between 10 and 20 nm 2 surface.…”
Section: Resultsmentioning
confidence: 99%
“…Considering BET surface areas and the molar mass of trypsin from bovine pancreas (23.8 kDa), each trypsin molecule in N1 and N2 occupies approximately 17 and 11 nm 2 of surface, respectively. Based on Saha et al [22] the molecular dimension of native trypsin from porcine pancreas is 4.8 nm x 3.7 nm x 3.2 nm. Assuming that the spatial dimensions of bovine-derived trypsin are similar and that enzyme molecules are surrounded by a hydration layer of approximately 0.2 nm, one trypsin molecule would occupy between 10 and 20 nm 2 surface.…”
Section: Yield Of Immobilized Trypsin In Imtrsmentioning
confidence: 99%
“…Due to these low coverage densities, the formation of multilayers is negligible and lateral interactions between adsorbed enzymes are rather weak. Saha et al [58] showed that the activity of trypsin on CuS nanoparticle depends on surface density. When trypsin molecules form a complete monolayer the 98% of the native enzyme activity was almost retained.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been found that the density of enzymes on the nanoparticle surface directly impacts the enzyme activity, which needs to be taken into account when using enzymatic conversions for label-free analyte detection. 62 Enzyme quantity and distribution were also established to be crucial in the performance of enzyme-powered nanomotors, where a certain threshold of enzyme numbers and asymmetric distribution was needed to generate nanoparticle motion. 18,19…”
Section: Articlementioning
confidence: 99%